Analysis of scientific production on environmental risk assessment in ecosystems with a circular economy - Yasniel Sánchez-Suárez; José Armando Pancorbo-Sandoval; Sonia Emilia Leyva-Ricardo; Verenice Sánchez-Castillo (Dyna)
Ecosystems are currently at risk, and scientific methods have been developed to assess these impacts. In this scenario, the circular economy makes it possible to reuse raw materials and reduce waste. The objective of the research is to analyze the scientific production related to the evaluation of environmental risks in ecosystems with a circular economy approach. Quantitative research was carried out, with a retrospective and descriptive approach, from a bibliometric study in the SCOPUS database in the period 2014 - 2024. The peak of research was 4, where research articles predominated with 7 in 12 areas of knowledge. The most producing country was the United States. The most producing journal was Thunderbird International Business Review with 159. four research lines and their gaps were identified. Environmental risk assessment is much more than a legal requirement; it is an opportunity to demonstrate an organization's commitment to sustainability.